PI3KC2α-dependent and VPS34-independent generation of PI3P controls primary cilium-mediated autophagy in response to shear stress - Asma Boukhalfa (Nature Portfolio, 2020)
The primary cilium is required for the autophagic response to shear stress. Here, the authors show that PI3KC2α has a role in ciliogenesis and promotes local PI3P production upon shear stress to induce autophagy that is distinct from VPS34-driven starvation-induced autophagy.